First-person shooter gaming simulator: article / Tajmalludin Yaakob - Yaakob, Tajmalludin (2012)
ln this paper, I have developed a device that worked with first-person shooter (FPS) game for personal computer (PC) platform. The idea of this project is to change the way of playing the FPS game from using the conventional method; mouse and keyboard to the real gun model. This project was using the Arduino Due as the microcontroller and the accelerometer ADXL335 as the main subject besides joystick and keyboard. This project also studies the behavior of The ADXL335 that can measure three types ofdata; acceleration, gravity and angle.